Factors associated with HIV testing among young women in Tanzania: Insights from the 2022 Tanzanian Demographic and Health Survey using Anderson’s Behavioral Model - Abebe, Mesfin; Asgedom, Yordanos Sisay; Gebrekidan, Amanuel Yosef; Wondimagegne, Yohannes Addisu; Hareru, Habtamu Endashaw; Tebeje, Tsion Mulat (Frontiers in Public Health, 2025)
BackgroundHIV continues to be a significant global health issue, particularly affecting sub-Saharan Africa, including Tanzania. Knowing one’s HIV status is a crucial first step in combating HIV/AIDS and achieving the targets set for the Sustainable Development Goals (SDGs) by 2030. However, despite ongoing efforts, HIV testing coverage remains low in developing countries, including Tanzania, where testing among young people poses particular challenges. Therefore, this study, based on the 2022 Tanzanian Demographic and Health Survey, aims to identify the factors influencing HIV testing among young women through the lens of Anderson’s Behavioral Model.MethodsIn this study, we analyzed a weighted sample of 5,810 young women from the 2022 Tanzania Demographic and Health Survey (TDHS). Given the hierarchical structure of the DHS data and the binary nature of the outcome variable ‘ever tested for HIV,’ we employed a multilevel mixed-effect logistic regression model. The best-fitting model was identified using the deviance value. In the multivariable analysis, we calculated adjusted odds ratios (AORs) along with their 95% confidence intervals (CIs) to assess the strength of associations between various predictors and HIV testing. Statistical significance was determined at a p-value of less than 0.05.ResultIn our study, the prevalence of HIV testing among young women was 60.18% (95% CI: 58.91 to 61.43%). Significant factors associated with HIV testing included age (AOR = 4.33, 95% CI [3.43, 5.45]), marital status (AOR = 2.31, 95% CI [1.76, 3.04]), knowledge of HIV prevention (AOR = 1.59, 95% CI [1.23, 2.04]), discriminatory attitudes towards HIV (AOR = 0.74, 95% CI [0.58, 0.95]), visiting healthcare facilities (AOR = 4.80, 95% CI [3.75, 6.14]), media exposure (AOR = 1.44, 95% CI [1.09, 1.90]), internet use (AOR = 1.56, 95% CI [1.02, 2.38]), and ever heard of STIs (AOR = 2.12, 95% CI [1.63, 2.77]).ConclusionOur study found that 60.18% of young women in Tanzania have been tested for HIV. Addressing barriers like stigma and improving access to healthcare and information through media and the internet can significantly boost HIV testing rates among young women, aiding the global effort to end the AIDS epidemic by 2030.The Anderson Behavioral Model emphasizes the importance of predisposing, enabling, and need factors in healthcare utilization, which aligns with our findings and underscores the necessity of a multifaceted approach to improve HIV testing rates.